Strengthening oxygen reduction activity and stability of carbon-supported platinum nanoparticles by fluorination. (10th December 2021) - Li, Ziheng; Sui, Lijun; Calvillo, Laura; Alonso-Vante, Nicolas; Ma, Jiwei
Highlights: Considering experimental and theoretical aspects, the ORR performance of Pt/F-C was compared with that of Pt/C. Improved strength and stability attained through the C-F bonds formed versus oxidation of the original CO and CC bonds. An increased charge transfer from Pt to the F-C support is at the origin of the strong metal-support interaction. Abstract: By combining experimental and theoretical aspects, this study focuses on exploring and enhancing the activity and stability towards oxygen reduction reaction (ORR) of fluorinated carbon supported platinum nanoparticles in the acidic electrolyte. Physical characterization results revealed that fluorinated carbon support generates a C-F bonding. The interaction between Pt and fluorinated-carbon allows for a strong charge transfer from Pt to the support. This phenomenon is consistent with the density functional theory (DFT) analysis. Because of the fluorination, the electronic structure of Pt is changed, which is an advantage for improving the catalytic activity and stability of the catalyst towards ORR. Graphical abstract: The ORR performance in Pt/F-C presented a significant improvement due to the adjustment of the electronic structure through the fluorinated carbon, and the formation of stronger C-F bonds versus the original CC bonds. Image, graphical abstract